Cytomorphological Assessment of FNAC Findings of Thyroid Swellings - Shalini Kashyap; Anil Kumar Gupta (Asian Journal of Medical Research, 2020)
Background: There is enormous burden of thyroid diseases in the general population. Among all the endocrine disorders, thyroid disorders are the most common in India. The present study was conducted to assess FNAC findings of thyroid swellings. Subjects and Methods: The present study was conducted on 108 patients with thyroid swellings. A thorough clinical examination was performed. USG findings were recorded in the available patients. FNAC was done as per standard protocols. Results: Out of 108 cases, males were 32 and females were 76. Common thyroid swelling was colloid nodular/adenomatous goitre seen in 57 patients followed by Lymphocytic Thyroiditis in 17 patients, simple colloid cyst in 12 patients, follicular neoplasm in 10 patients, toxic goiter (grave’s disease) and papillary carcinoma in 03 patients each with insufficient material obtained in 06 patients. The difference was significant (P< 0.05). Conclusion: Authors found that most common thyroid swelling was colloid nodular/adenomatous goitrefollowed by lymphocytic thyroiditis with sensitivity of FNAC found to be 73.5%.